2010
DOI: 10.1002/jcb.22546
|View full text |Cite
|
Sign up to set email alerts
|

A novel zinc finger protein Zfp637 behaves as a repressive regulator in myogenic cellular differentiation

Abstract: Zinc finger proteins have been implicated as transcription factors in the differentiation and development of cells and tissues in higher organisms. The classical C2H2 zinc finger motif is one main type of motif of zinc finger proteins. Our previous studies have shown that Zfp637, which comprises six consecutively typical and one atypical C2H2 zinc finger motifs, is highly expressed in undifferentiated or poorly differentiated cell lines, but is moderately or slightly expressed in normal tissues. We have also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In addition, tissue-specific expression of Zfp637 has been correlated with telomerase activity1, and thus, it may be involved in multiple biological behaviors. In our previous studies, we confirmed that Zfp637 could repress myogenic cellular differentiation2, but the specific functions of Zfp637 in germ cell differentiation remain unknown. In this study, we examined the expression of Zfp637 in mouse spermatogonia and then evaluated the effects of Zfp637 overexpression or underexpression on germ cell differentiation.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In addition, tissue-specific expression of Zfp637 has been correlated with telomerase activity1, and thus, it may be involved in multiple biological behaviors. In our previous studies, we confirmed that Zfp637 could repress myogenic cellular differentiation2, but the specific functions of Zfp637 in germ cell differentiation remain unknown. In this study, we examined the expression of Zfp637 in mouse spermatogonia and then evaluated the effects of Zfp637 overexpression or underexpression on germ cell differentiation.…”
supporting
confidence: 53%
“…According to a bioinformatics analysis, the zinc finger transcription factor protein Zfp637 may play a role in gene regulation, thus impacting the biological behavior of cells. Our previous study has also confirmed that Zfp637 plays an important role in the differentiation of cells2. Consequently, immunocytochemistry (ICC) was performed to detect the expression of Zfp637 in mouse spermatogonial GC-1 spg cells.…”
Section: Resultsmentioning
confidence: 76%
“…51 In a previous report, we hypothesized that Zfp637 may directly regulate mTERT by interacting with the core promoter region or indirectly promote mTERT transcription by regulating or synergistically cooperating with Sp1 and Sp3. 24 In this study, we demonstrated that Zfp637 binds to the mTERT promoter (−535/−502) specifically and activates the transcription of mTERT directly. However, the sequence of the Zfp637-binding site has not yet been elucidated and further experiments are needed to explore the Zfp637-responsive elements.…”
Section: Discussionmentioning
confidence: 55%
“…41 Our previous investigation demonstrated that Zfp637 promotes myogenic cellular proliferation and inhibits cellular differentiation by upregulating mTERT. 24 However, the mechanism underlying the regulation of mTERT by Zfp637 has not been previously elucidated. In this study, we focused on the relationship between Zfp637 and mTERT in the model of oxidative stress-induced premature senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation